Barriers to the implementation of value management in small construction projects. (15th August 2022) - Lin, Xiaobin; Mazlan, Ain Naadia; Ismail, Syuhaida
Abstract: As a well-established approach for attaining cost-effectiveness and value for money, Value Management (VM) is often overlooked in small construction projects, particularly in developing countries. This paper takes Malaysia as a case study to investigate the barriers to implementing VM in small construction projects with a view to exploring possible measures in mitigating the barriers and improving VM usage in small projects. Construction practitioners directly involved in small projects were surveyed using a structured questionnaire. Results of the survey revealed that the frequency with which the practitioners implement VM for small projects remains relatively low. Barriers contributing to this can be categorized under the knowledge and guidance barriers, environmental barriers, resource barriers, methodological barriers, and cultural barriers. Significant barriers were found mainly associated with the knowledge, guidance, and environment of disseminating the approach in small construction projects. Furthermore, measures that are perceived viable in overcoming the barriers were discussed. The findings of this paper provide a favorable reference for participants of small construction projects in VM decision and implementation in Malaysia as well as other countries with similar situations. As little empirical study focused on VM in small construction projects, this paper also contributes to enriching the body of knowledge related to the management of small projects. Highlights: Current adoption and barriers of value management in small construction projects are investigated in the study. 21 barriers inhibiting the adoption of value management in small construction projects are assessed. Underlying attributes of the barriers to value management in small construction projects are explored. Viable measures for mitigating barriers and improving usage of value management are suggested.